Effect of central screw taper angles on the loosening performance and fatigue characteristics of dental implants. (May 2022) - Sun, Fei; Lv, Li-Tao; Xiang, Ding-Ding; Ba, De-Chun; Lin, Zeng; Song, Gui-Qiu
Abstract: Biomechanical performance plays an important role in the long-term service of dental implants. Loosening and fatigue damage of the central screw are the most common problems. This research investigated the effect of the central screw taper angle on the loosening performance and fatigue characteristics of dental implants. Central screws with four taper angles, 30°, 60°, 90° and 180°, were processed and tested. The loosening performance of the screws under initial and postload conditions was compared. Then, the fatigue characteristics of dental implants was measured. Finally, the wear and fracture modes of the screws were observed. The damage locations were verified by finite element analysis (FEA). The results showed that the central screws with 30° taper had substantially better anti-loosening performance and less fretting wear. The central screws with 180° taper had a higher preload, resulting in a longer fatigue life. Furthermore, the fatigue fracture of the central screw occurred at the level of the first thread position, consistent with the FEA results. In the future clinical applications, central screws with a 30° taper angle may improve anti-loosening performance and prolong fatigue life by increasing the tightening torque. Graphical abstract: Image 1 Highlights: Four types of central screws with different mating taper angles were manufactured. Reduction of the central screw taper improves resistance of dental implants to loosening. A central screw with a high preload increases the fatigue life of dental implants. Reduction of the central screw taper results in less surface wear after cyclic loading. The fatigue fracture of the central screw mainly occurs at the level of the first thread.